2018
DOI: 10.1108/jfmm-04-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Shopping channel preference and usage motivations

Abstract: Purpose The purpose of this paper is to provide a greater understanding of why and how different ages use shopping channels, analysing preferences and motivations for use. Design/methodology/approach Qualitative in-depth interviews were conducted with a sample of 50 female participants, aged 20-70. All were customers of a fashion retailer that has ecommerce and mcommerce platforms, stores and catalogues, in order to gain a better understanding of loyal consumers’ multi-channel behaviour. Findings Multi-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 31 publications
3
32
0
4
Order By: Relevance
“…In particular, consumers engage in webrooming for the purpose of information attainment and price comparison. The findings lend support to the qualitative work by Boardman and McCormick (2018) which indicated that webrooming can occur when consumers' feel sceptical about the product information found online. Interestingly, while Kang (2018) also revealed that while webroomers are motivated to gather product information, they are not, however interested in using webrooming as a means for price comparison.…”
Section: Literature Reviewsupporting
confidence: 73%
See 1 more Smart Citation
“…In particular, consumers engage in webrooming for the purpose of information attainment and price comparison. The findings lend support to the qualitative work by Boardman and McCormick (2018) which indicated that webrooming can occur when consumers' feel sceptical about the product information found online. Interestingly, while Kang (2018) also revealed that while webroomers are motivated to gather product information, they are not, however interested in using webrooming as a means for price comparison.…”
Section: Literature Reviewsupporting
confidence: 73%
“…As a matter of fact, channels should be treated as complementary in nature. The exhibition of cross-channel shopping behavior is primarily to help consumers to minimize discrepancies between channels (Boardman & McCormick, 2018). To clarify, consumers find that different channels offer additional values, and are thus driven to approach a particular channel for what it excels at (Kalyanam & Tsay, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to much inappropriate online media regarding their reputation and behaviour (Wijaya, 2019) so it is risky for brand communication, offline or physical shopping is considerably more 'comfortable' and 'safe' related to sensorial experiences, interpersonal communication, and after-sales service (Vroom, 2016). Wei-yu and Zhen in Yu, Sun, and Guo (2019) suggest some concerns regarding consumer preferences for in-store channels, including price, quality, comfort, accessibility, services provided, and product variations, while Boardman and Mccormick (2018) suggest convenience and enjoyment as consumer preferences for physical store channel, and convenience, selection, adventure/ exploration and idea shopping for the ecommerce shopping channel. due to its influence on product sales, especially in the mass commodity market, where self-service is the rule, and the store becomes the main decision-making centre in the selection of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Os consumidores idosos buscam por conveniência em suas compras e tendem a procurar locais onde possam resolver todas as compras de uma só vez (Rahman & Yu, 2018). Por esse motivo costumam frequentemente fazer compras lojas de departamentos e em lojas físicas localizadas na proximidade de suas casas (Boardman & McCormick, 2018;Lopes et al, 2013).…”
Section: Consumo Na Terceira Idadeunclassified
“…Gilleard, 2018;Hettich et al, 2017;Scaraboto & Fischer, 2013;Twigg, 2007 Local de compra Descrevem os locais de compra de itens de vestuário. Boardman & McCormick, 2018;Hettich et al, 2017;Lopes et al, 2013;Townsend et al, 2019 Produto -utilitário Descreve características utilitárias dos itens de vestuário. Guido et al;2014;Howarton & Lee, 2010;Lee et al, 2012;Rahman & Yu, 2018 Produto -hedônico Descreve características hedônicas dos itens de vestuário.…”
Section: Descrição Referencial Teóricounclassified